2017
DOI: 10.1515/opag-2017-0047
|View full text |Cite
|
Sign up to set email alerts
|

Performance of informal market sweet potato cultivars in on-farm trials in South Africa

Abstract: Several new sweet potato cultivars have been released in South Africa from 2004 until 2011 with varietal traits suitable for the informal market. This paper reports on results of on-farm trials conducted to evaluate the cultivars in broader agro-ecologies in the country. The trials were conducted at 15 localities across the 2011/12 to 2014/15 planting seasons including six cultivars with varying flesh colours. Data collection included marketable and unmarketable storage root yield classes, dry mass, and taste … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…They were among the progeny of the first set of crosses conducted among elite parental lines imported from CIP, Peru. This first series of crosses were referred to as the “A” series, and proved the most successful with seven crosses being released and grown by small and large-scale farmers [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…They were among the progeny of the first set of crosses conducted among elite parental lines imported from CIP, Peru. This first series of crosses were referred to as the “A” series, and proved the most successful with seven crosses being released and grown by small and large-scale farmers [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…22,41 Multiple studies have shown that African consumers typically prefer sweet potatoes with high dry matter and low water content. 4244 A choice experiment conducted in 2008 in 2 provinces of Mozambique revealed that willingness to pay for high dry matter content (associated with a firm, starchy potato) was almost twice that of willingness to pay for the color of pulp, even when consumers received information about the health benefits of consuming OFSP. 22,41 The Resisto variety has been shown to be popular in Mozambique due to its taste, dark-orange color, growth structure, and high yields but was found to be less drought-tolerant than the light-orange Jonathan variety.…”
Section: Discussionmentioning
confidence: 99%
“…van Vugt and Franke (2018) defined attainable yield as the mean onfarm yield plus three times the standard deviation and found that attainable root yields varied from 18 to 32 t ha −1 among districts in Malawi. Attainable root yields in experimental farms under rainfed conditions were 25 t ha −1 in Cameroon (Yengoh and Ardo, 2014), 25-29 t ha −1 in South Africa (Laurie et al, 2017), 27 t ha −1 in Mozambique (Andrade et al, 2017b), 27-32 t ha −1 in Rwanda (Rukundo, 2015) and 39 t ha −1 in Nigeria (Uwah et al, 2013). Despite the reputation of sweetpotato as a robust crop tolerant to low inputs and minimal crop management, based on these numbers it appears that a 100-200% yield increase can realistically be obtained with improved crop management (Oswald et al, 2009).…”
Section: Sweetpotato Yield Gaps In Ssamentioning
confidence: 95%
“…There has been meager research regarding the critical understanding of the water requirement and use efficiency of sweetpotato (Gomes and Carr, 2003;Gomes et al, 2005;Laurie et al, 2017). An important proxy for the water requirements of a crop is the crop coefficient (Kc), which relates crop water requirement to the reference evapotranspiration figure of a given area 7 .…”
Section: Water Managementmentioning
confidence: 99%
See 1 more Smart Citation